The Relationship of Socioeconomic and Behavioral Risk Factors With Trends of Overweight in Korea - Jin Hee Shin (Journal of Preventive Medicine and Public Health, 2015)
Objectives: Previous studies have shown that overweight (including obesity) has increased significantly in Korea in recent decades. However, it remains unclear whether this change has been uniform among all Koreans and to what extent socioeconomic and behavioral factors have contributed to this increase. Methods: Changes in overweight were estimated using data from the 1998, 2001, 2005, 2007-2009, and 2010-2012 Korea National Health and Nutrition Examination Survey (n=55 761). Results: Overweight increased significantly among men but not among women between 1998 and 2012. Changes in socioeconomic and behavioral factors over the time period were not associated with overall trends for both men and women. However, we found significant differences in the prevalence of overweight relative to key risk factors. For men, overweight increased at a significantly greater rate among the non-exercising (predicted probability [PP] from 0.23 to 0.32] and high-calorie (PP from 0.18 to 0.37) groups compared to their active and lower-calorie counterparts, respectively. For women, overweight increased only among the non-exercising (PP from 0.27 to 0.28) and low-income (PP from 0.31 to 0.36) groups during this period. Conclusions: These findings suggest that programs aimed at reducing overweight should target Korean men and women in specific socioeconomic and behavioral risk groups differentially.